Progressive orbital granular cell tumour associated with medial rectus. (3rd September 2017) - Yang, David; McLaren, Sally; Van Vliet, Chris; deSousa, Jean-Louis; Gajdatsy, Adam
ABSTRACT: Granular cell tumour is a rare soft tissue tumour that can occur in any part of the body, but seldom in ocular adnexa. It usually behaves in a benign fashion. We report a case of a 54-year-old man with a well-demarcated, solitary, slow-growing orbital tumour which lead to significant ocular symptoms. The case was a diagnostic and therapeutic challenge due to its location and difficulty in obtaining tissue for a histological diagnosis. Surgical biopsy attempts were made but they all failed to uncover the true identity of the lesion. A definitive diagnosis was revealed with complete surgical excision of the tumour, which was challenging due to its size and close association with rectus muscle. This case has highlighted that orbital granular cell tumour may result in significant ocular symptoms. Adequate exposure to the anatomical site is the key to obtaining diagnosis and complete excision of a lesion.